2006
DOI: 10.1039/b605105g
|View full text |Cite
|
Sign up to set email alerts
|

Reversible lithium insertion and copper extrusion in layered oxysulfides

Abstract: All of the copper in the layered oxysulfides Sr2MnO2Cu1.5S2 and Sr2MnO2CU3.5S3 may be extruded as the element and the copper ions replaced quasi-reversibly by lithium ions in reductive topotactic ion exchange reactions; dramatic changes in magnetic properties result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 15 publications
5
52
0
Order By: Relevance
“…The PXRD study of the cycled anodes at various discharge potentials given in Figure 5a have the species present as indicated in equation (1). [36] As the anode is discharged to lower potential, the CTS NPs dissociate further and upon the total discharge to 0.01 V, the sharp peaks of Li x Sn, Li 2 S and Cu metal which is a buffer matrix imply the total conversion of the material. [36] As the anode is discharged to lower potential, the CTS NPs dissociate further and upon the total discharge to 0.01 V, the sharp peaks of Li x Sn, Li 2 S and Cu metal which is a buffer matrix imply the total conversion of the material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PXRD study of the cycled anodes at various discharge potentials given in Figure 5a have the species present as indicated in equation (1). [36] As the anode is discharged to lower potential, the CTS NPs dissociate further and upon the total discharge to 0.01 V, the sharp peaks of Li x Sn, Li 2 S and Cu metal which is a buffer matrix imply the total conversion of the material. [36] As the anode is discharged to lower potential, the CTS NPs dissociate further and upon the total discharge to 0.01 V, the sharp peaks of Li x Sn, Li 2 S and Cu metal which is a buffer matrix imply the total conversion of the material.…”
Section: Resultsmentioning
confidence: 99%
“…The PXRD plot at 1.4 V shows the onset of Li x Sn [34] formation along with the peaks of Li 2 S [35] species formation and Cu metal. [36] As the anode is discharged to lower potential, the CTS NPs dissociate further and upon the total discharge to 0.01 V, the sharp peaks of Li x Sn, Li 2 S and Cu metal which is a buffer matrix imply the total conversion of the material. The FTIR spectroscopy done on the anodes cycled at two selected potentials 0.6 and 0.01 V reveals the electrolyte decomposition due to SEI formation as well as the Li 2 S evolution as evident from Figure 5b.…”
Section: Resultsmentioning
confidence: 99%
“…The phase identification refers to the research results of Zlatkov, et al [9], Rutt, et al [10], Al-Saie, et al [11], and Jankovskýa, et al [12] for the phase of barium hexa-ferrite (BaFe 12 O 19 ), strontium oxide (SrO), hematite (Fe 2 O 3 ), and manganese oxide (Mn 2 O 3 ), respectively. The refinement result, revealed that manganese substitution in the iron atoms was only able to reach the limit of z = 1.…”
Section: Methodsmentioning
confidence: 99%
“…We applied [35] ** *All electron basis set; **46e 2 -ECP. [36] 6.770 [23,37] 6.575 6.562 Rb 2 O 6.756 [38] 6.899 [23,39] 6.738 6.792 SrO 5.133 [40] 5.177 [24,39] 5.156 5.185 SrCl 2 6.971 [41] 6.062 [24,37] 7.018 6.99 Y 2 O 3 10.604 [42] 10.637 [25,39] 10.595 10.607 ZrO 4.602 [43] 4.581 [26,39] 4.566 4.559 RuO 4 8.509 [44] 9.256 [29,39] 8.517 8.532 Ag 2 O 4.724 [45] 4.769 [31,39] 4.741 4.725 AgCl 5.549 [46] 5.633 [31,37] 5.471 5.47 CdO 4.684 [47] 4.746 [32,39] 4.681 4.687 CdO 2 5.313 [48] 5.365 [32,39] 5.311 5.306 CdF 2 5.389 [49] 5.457 [32,50] 5.35 5.391 In 2 O 3 10.122 [51] 10.191 [33,39] 9.964 10.118 InSb 6.479 [52] 6.531 [33] 6.222 6.357 KI 7.049…”
Section: Computational Detailsmentioning
confidence: 99%
“…The results are given in Table 7 with the corresponding relative errors to the HF-limits in Figure 4. It could be shown that both basis sets are applicable [36] 6.863 6.922 [23,37] 6.727 6.695 SrO 5.133 [40] 5.219 5.230 [24,39] 5.203 5.227 Y 2 O 3 10.604 [42] 10.692 10.761 [25,39] 10.709 10.722 CdO 4.684 [47] 4.746 4.778 [32,39] 4.708 4.721 In 2 O 3 10.122 [51] 10.117 10.126 [33,39] 9.995 10.084 SnO 2 (a) 4.740 [58] 4.721 4.662 [34,39] to HF calculations of solids. The HF results for lattice constants are slightly worse than for PW1PW for pob-TZVP basis sets but are still satisfying.…”
Section: Hf Calculationsmentioning
confidence: 99%